2012
DOI: 10.1111/j.1440-1681.2012.05672.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cardiac M3 muscarinic acetylcholine receptors has cardioprotective effects against ischaemia‐induced arrhythmias

Abstract: Increasing evidence indicates the important roles of M(3) muscarinic acetylcholine receptors (M(3) mAChR) in the regulation and maintenance of cardiac function and heart disease. In the present study, we investigated whether the M(3) mAChR mediates the cardioprotection against ischaemia-induced arrhythmias and the mechanisms involved. Myocardial ischaemia was established in Wistar rats by occlusion of the left anterior descending coronary artery. Rats were treated with choline chloride (an M(3) mAChR agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…29 Moreover, previous studies have demonstrated that choline, an agonist of M3AChR, reduces intracellular Ca 2+ overload in cardiomyocytes. [30][31][32] However, additional studies are required to identify the link between M3AChR and attenuation of Ca 2+ overload. We further explored the signaling pathway mediated by acetylcholine in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, previous studies have demonstrated that choline, an agonist of M3AChR, reduces intracellular Ca 2+ overload in cardiomyocytes. [30][31][32] However, additional studies are required to identify the link between M3AChR and attenuation of Ca 2+ overload. We further explored the signaling pathway mediated by acetylcholine in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a precursor molecule of neurotransmitter acetylcholine, studies have clarified that choline exhibited beneficial effects on several cardiac diseases including myocardial infarction [18], ischemic arrhythmias [19], IR injury [20] and cardiac hypertrophy [21]. Meanwhile, previous studies have revealed that choline reduced infarct size and prevented ischemic arrhythmias by inhibiting cardiomyocyte apoptosis as well as preserving phosphorylated connexin43 and regulating ion channels including L-type Ca 2+ channel and Na + /Ca 2+ exchanger [18-20].…”
Section: Introductionmentioning
confidence: 99%
“…M 3 -mAChR protects the heart against hypertrophy by downregulating the expression of AT1 receptor [38], normalizing the deregulated expression of miR-133a [14], and upregulating the expression of phospho-p38 and calcineurin [39]. Probably, the most pertinent to the present study is the finding that M 3 -mAChR can produce anti-arrhythmic effects in ischemic hearts through downregulating miR-1 expression along with upregulation of Kir2.1 levels and reducing Ca 2+ overload mediated by enhanced L-type Ca 2+ channels and NCX [13]. Here our findings add to the beneficial profile of M 3 -mAChR with its anti-arrhythmic properties in the setting of CH.…”
Section: Discussionmentioning
confidence: 88%
“…Among these various regulators, the M 3 subtype of muscarinic acetylcholine receptors (M 3 -mAChR) has been noticed in recent years for its role in modulating cardiac function under physiological and pathological conditions [13-15]. M 3 -mAChR, which was once believed to be absent in myocardium, has not long ago been identified for its existence in the heart of various species, including man [16, 17].…”
Section: Introductionmentioning
confidence: 99%